(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article summarizes the cultural and practical life of the Soviet Union, which analyzes the role of women and their direct participation in cultural reforms. It can be said that during the Soviet era, women served as a source of childcare and the development of local culture, despite the fact that there were many barriers and unnecessary restrictions not only in social but also in cultural and educational fields.